Equoterapia como recurso terapêutico na mielomeningocele: Um estudo de caso - Gomes, Tatiane Targino [UNESP]; Hassunuma, Renato Massaharu; Da Silva, Luciana Marçal (Universidade Federal de Sao Paulo, 2014)
Objective. To evaluate the gain of muscle strength and functional independence of a female patient with myelomeningocele and hydrocephalus, performing hippotherapy. Method. 31 weekly sessions of hippotherapy lasting 30 minutes each; at the first evaluation it was applied the Sensitivity Test; the Muscular Strength Test and the Functional Independence Measurement Form were applied at the beginning and after 3, 6 and 10 months of treatment. Results. The Sensitivity Test rated the lesion level at T10, classifying it as a complete lesion, with no motor or sensory function in sacral segments; the Muscle Strength Tests showed strength gains in some muscles, which enabled improvement in the functional independence of the patient. Conclusion. Based on the noted significant improvement in muscle and functional condition of the studied practitioner, it is suggested further research in order to contribute to establish the hippotherapy as a therapeutic method in myelomeningocele treatment.
Hippotherapy as a therapeutic resource in myelomeningocele: A case study
Keywords: Equine-assisted therapy; Muscle strength; Myelomeningocele